Pengaruh Persepsi Pengguna terhadap Penerimaan dan Kepuasan Aplikasi Sayang Warga Surabaya Berdasarkan Model Technology Acceptance Model (TAM) - Anwar, Sulthan Rafi; Bingamawa, Muhammad Tosan; Ardieansyah, Ardieansyah (sudo Jurnal Teknik Informatika, 2025)
The low level of digital literacy, the usage gap among Kader Surabaya Hebat (KSH), and the mismatch between the perceived benefits and technical ease of use indicate problems in the adoption of the Sayang Warga application in Surabaya City. These issues have led to inconsistent data input from KSH, hindering the optimization of digital public services. This study aims to analyze the level of user acceptance and satisfaction toward the Sayang Warga application using the Technology Acceptance Model (TAM). The research employed a quantitative method with an inferential approach. Data were collected through questionnaires distributed to active users of the application, namely KSH, using a simple random sampling technique. The data analysis was conducted using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method. The results showed that the application is perceived as useful in accelerating administrative services (perceived usefulness), easy to learn and operate (perceived ease of use), and users expressed positive attitudes and satisfaction (attitude toward using). Furthermore, users demonstrated a strong intention to continue using the application (behavioral intention to use), and most of them have actively used it (actual use), although some technical obstacles remain. The study concludes that there is a need to enhance digital training for KSH, simplify the application interface, and strengthen feature integration so that the Sayang Warga application can be more optimally utilized to improve the quality of public services in Surabaya City.